1995
DOI: 10.2165/00003088-199500292-00006
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Plasma Protein Binding of Zileuton and its N-Dehydroxylated Metabolite

Abstract: An ultrafiltration technique or equilibrium dialysis has been used to study the in vitro human plasma protein binding of racemic zileuton, its individual enantiomers, and its pharmacologically inactive metabolite N-dehydroxyzileuton.The plasma protein binding of zileuton and N-dehydroxyzileuton over the concentration range of 0.1 to 100 mg/L averaged 93.1 ± 0.22 and 92.0 ± 0.12%, respectively. However, there appeared to be a stereoselective effect, with the R( +) enantiomer of zileuton demonstrating greater bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Use of C max (19 M) and C ave (9.0 M) values for total zileuton in plasma (Awni et al, 1995a) resulted in overestimates of AUC changes (data not shown). After correction for binding of zileuton (f u ϭ 0.069) to human plasma proteins (Machinist et al, 1995a), more reasonable estimates of AUC ratios were obtained (Fig. 4).…”
Section: The K I Values For (S)-(ϫ)-and (R)-(ϩ)-zileuton Were Comparamentioning
confidence: 85%
See 2 more Smart Citations
“…Use of C max (19 M) and C ave (9.0 M) values for total zileuton in plasma (Awni et al, 1995a) resulted in overestimates of AUC changes (data not shown). After correction for binding of zileuton (f u ϭ 0.069) to human plasma proteins (Machinist et al, 1995a), more reasonable estimates of AUC ratios were obtained (Fig. 4).…”
Section: The K I Values For (S)-(ϫ)-and (R)-(ϩ)-zileuton Were Comparamentioning
confidence: 85%
“…Because dmd.aspetjournals.org the concentrations of both enantiomers in plasma are similar (Wong et al, 1995), the in vitro data suggest that the (S)-enantiomer may play more of a role in vivo. However, f u is higher (0.122 versus 0.037) for the (R)-enantiomer (Machinist et al, 1995a), which could offset the difference in the k inact /K I ratio. Based on the results of this study, it is concluded that zileuton is a dmd.aspetjournals.org weak reversible inhibitor of P450 activities in human liver microsomes.…”
Section: Fig 2 Concentration-and Time-dependent Inactivation Of Podmentioning
confidence: 93%
See 1 more Smart Citation
“…Among those, equilibrium dialysis, gel-filtration, ultra-filtration and ultra-centrifugation [16,[24][25][26][27][28] have been conventionally and most commonly used. These conventional methods suffer from long analysis time.…”
Section: Introductionmentioning
confidence: 99%
“…Among those, equilibrium dialysis and ultrafiltration followed by HPLC analysis have been conventionally and most commonly used [7][8][9][10]. Equilibrium dialysis separates molecules across a semipermeable membrane according to molecular size (weight) by utilizing the driving force of concentration differential between solutions on each side of the membrane.…”
Section: Introductionmentioning
confidence: 99%